Miradas cruzadas en la repatriación de saberes. El caso de las grabaciones rituales náayeri registradas por K. Th. Preuss - Margarita Valdovinos Alba (Journal de la Société des Américanistes, 2020)
In 1906 the German ethnologist Konrad Theodor Preuss recorded Náayeri ceremonial chants in more than 43 wax cylinders. At the end of last century, this collection was accessible only for a specialized public in the Berlin Phonographic Archive. A large research project was conducted in order to allow access to these wax cylinders by presenting their content to Náayeri ritual experts, preparing its edition and distributing CD’s with a selection of historic chants among the members of the Náayeri community from where the recordings were originally made. In this paper, I will analyze the retribution process of this ancient collection of chants in which the Náayeri ritual specialists have played an active role. My study will also consider the impact that this repatriation process had on the documentation of contemporary versions of the same kind of Náayeri ceremonial chants and its subsequent edition.